Analysis of Factors Influencing Repurchase Decision at Rulyprint Printing Services - Natalia, Jennifer; Kaihatu, Thomas Stefanus (Universitas Ciputra Surabaya, 2023)
The purpose of this thesis research is to find out what factors influence consumer repurchase decisions at Rulyprint printing. The research method used is confirmatory factor analysis to test and confirm a group of latent variables assumed at the beginning of the study. The sampling technique used non-probability sampling with a saturated sample of 53 respondents where the entire population was used as a sample in this study. From the results of the study, it was confirmed that five factors were formed that influenced consumer repurchase decisions at Rulyprint printing. The first factor is consumer perception with five indicators in it, namely attitudes, motives, interests, experiences, and expectations. The second factor is service quality with five indicators that influence tangibility, reliability, responsiveness, assurance, and empathy. The third factor is perceived value with four indicators, namely performance, value for money, emotional value, and social value. The fourth factor is trust with three influencing indicators, namely ability, benevolence, and integrity. Finally, the fifth factor is switching cost with three indicators, namely procedural switching cost, financial switching cost, and relational switching cost. The first factor has the highest influence with a percentage of 36.136%, the second factor is 13.638%, the third factor is 10.100%, the fourth factor is 6.062%, and the fifth factor is 5.161%. These factors have a total variance of 71.097%.